Andrographolide Derivative AL-1 Ameliorates LPS-induced Acute Lung Injury by Inhibiting NLRP3 Inflammasome and Lung Permeability - Li, Tangjia; Zhang, Chu; Wei, Yuke; Zhong, Haijing; Shan, Luchen; Yu, Pei; Wang, Yuqiang; Xu, Lipeng (Current Pharmaceutical Design, 2022)
Background: Acute lung injury (ALI) is a serious respiratory disease with a high mortality rate, and there is an urgent need for a more effective treatment strategy. Andrographolide derivative AL-1 has been identified to possess anti-inflammatory activity. However, whether it could reduce LPS-induced lung injury in mice through inhibiting NLRP3 inflammasome activation and protecting lung permeability has not yet been elucidated. In the present research, we investigated the protective effect of AL-1 on ALI mice and demonstrated the potential mechanisms. Methods: Male Balb/c mice were anesthetized with isoflurane, and ALI mice were induced by intratracheal instillation of LPS. The mice were euthanized after LPS administration for 12 h, then bronchoalveolar lavage fluid (BALF) and lung tissues were collected. The levels of inflammatory factors were measured by ELISA assay, and HE staining and lung injury scoring were used to evaluate the pathological changes in the pulmonary tissues. Immunohistochemistry and immunofluorescence examination were conducted to detect the expression levels of related proteins. Western blot was performed to measure the levels of NLRP3 inflammasome and tight junction proteins. Results: The study indicated that AL-1 effectively alleviated lung injury by reduction of proinflammatory cytokine levels, MPO activity, lung W/D ratio, and total protein levels. Furthermore, AL-1 improved pathological changes in lung tissue and significantly reduced the infiltration of inflammatory cells. Administration with AL-1 markedly inhibited the expression of NLRP3, ASC, Caspase-1, IL-1β, gasdermin D (GSDMD), and VCAM-1 but increased the expression of ZO-1, Occludin, JAM-A, and Claudin-1. Conclusion: Taken together, these results demonstrated that AL-1 ameliorated pulmonary damage by inhibiting the activation of the NLRP3 inflammasome pathway and restoring TJ protein expression.
Keywords: cytokines